2011
DOI: 10.1007/s00248-011-9803-1
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of Fungi on Decomposing Woody Litter in a Freshwater Stream, Western Ghats, India

Abstract: We mapped filamentous fungal association with mechanically "hard" and "soft" woody litter naturally deposited in a stream of the Western Ghats of India. Using a durometer (rubber hardness tester), the toughness of surface of wood collected from stream was determined by considering durometer reading from 60-72 to 30-37 as hardwood and softwood, respectively. From each wood (1.5 cm diameter), two segments each of 3 cm length were excised and vertically cut into nine sections comprising eight marginal and one cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Fungi and bacteria interact synergistically and antagonistically during leaf breakdown (Gulis and Suberkropp, 2003b;Sridhar and Sudheep, 2011). In the present study, the highest values of ATP were found in the final stages of decomposition, although with fluctuations over time and higher concentrations of ergosterol.…”
Section: Contribution Of Microorganismsmentioning
confidence: 69%
See 1 more Smart Citation
“…Fungi and bacteria interact synergistically and antagonistically during leaf breakdown (Gulis and Suberkropp, 2003b;Sridhar and Sudheep, 2011). In the present study, the highest values of ATP were found in the final stages of decomposition, although with fluctuations over time and higher concentrations of ergosterol.…”
Section: Contribution Of Microorganismsmentioning
confidence: 69%
“…As shown in several studies (Gessner and Van Ryckegem, 2003;Krauss et al, 2011;Sridhar and Sudheep, 2011), the changes in physical and chemical characteristics of the detritus during the decomposition process may have changed the abundance of fungal species in the community, with fungi capable of degrading recalcitrant compounds becoming more abundant.…”
Section: Contribution Of Microorganismsmentioning
confidence: 97%
“…Lotic fungal diversity was greater on softwood than hardwood. Jaccard's index of similarity was greater for in lignicolous fungi than Ingoldian fungi in hardwood and softwood, suggesting that lignicolous fungi dominated hardwood and Ingoldian fungi dominated softwood (Sridhar and Sudheep 2011). Fecal pellets of…”
Section: The Aquatic Hyphomycetementioning
confidence: 95%
“…Geographical distribution and substrate known: Phaeoisaria clavulata has been widely collected in different European localities (Ellis, 1971;Révay, 1986). There are also reports from Malawi (Sutton, 1993), India (Rao & De Hoog, 1986;Sridhar & Sudheep, 2011), Malasya (Cybernome, 2017) and Pakistan (Abbas et al, 2013). It is considered a lignicolous species.…”
Section: Taxonomic Summarymentioning
confidence: 99%